Effect of lightcuring duration on color change of nanofiller composite resin on red grape juice immersion - Monik Aprilia Putri; Eko Hadianto; Grahita Aditya (Jurnal Medali, 2023)
Background: One of the aesthetic issues in the use of composite resin is the color change. The study aims to compare the color changes of nanofiller composite resin before and after immersion in red grape juice with different curing durations.Method: This study involved 18 round composite resins with a diameter of 12 mm and a thickness of 2 mm. The sample was divided into three groups (n=6); group A was cured for 20 seconds, group B for 30 seconds, and group C for 40 seconds. After curing, the samples were immersed in artificial saliva at 37°C for 24 hours before being measured by UV-vis spectrophotometer. The three groups were immersed in red grape juice for three days and the final color was measured. Data were analyzed using One Way Anova and Post Hoc LSD.Result: The One Way Anova test showed a significance value of 0.000, meaning (p < 0.05) it was said that there was a significant difference in each group followed by a post hoc LSD test on composite resin cured for 20 seconds against 30 seconds. second group and 40 seconds to get a significant differenceConclusion: Longer curing duration can defend nanofiller composite resin against discoloration due to the consumption of grape juice.